Designing audio power amplifiers - Cordell, Bob (Routledge, 2019)
"This comprehensive book on audio power amplifier design will appeal to members of the professional audio engineering community as well as the student and enthusiast. Designing Audio Power Amplifiers begins with power amplifier design basics that a novice can understand and moves all the way through to in-depth design techniques for very sophisticated audiophile and professional audio power amplifiers. This book is the single best source of knowledge for anyone who wishes to design audio power amplifiers. It also provides a detailed introduction to nearly all aspects of analog circuit design, making it an effective educational text. Develop and hone your audio amplifier design skills with in-depth coverage of these and other topics: Basic and advanced audio power amplifier design Low-noise amplifier design Static and dynamic crossover distortion demystified Understanding negative feedback and the controversy surrounding it Advanced NFB compensation techniques, including TPC and TMC Sophisticated DC servo design MOSFET power amplifiers and error correction Audio measurements and instrumentation Overlooked sources of distortion SPICE simulation for audio amplifiers, including a tutorial on LTspice SPICE transistor modeling, including the VDMOS model for power MOSFETs Thermal design and the use of ThermalTrakTM transistors Four chapters on class D amplifiers, including measurement techniques Professional power amplifiers Switch-mode power supplies (SMPS)"--